EFEKTIVITAS MEDIA POWTOON DALAM MENINGKATKAN PEMBELAJARAN PAI DI SMP NEGERI 2 BEKASI - Chasanah, Amelia; Fauziyah, Nur Laily; Hidayatullah, M Agung (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
In today's digital era, the use of innovative learning media is becoming increasingly important to increase the effectiveness of the learning process. This study aims to determine the application of powtoon media in Islamic religious education learning activities and to determine the effectiveness of powtoon media in improving Islamic Religious Education learning at SMPN 2 Bekasi. The research method used is quantitative, with a one group pretest-posttest design. Data collection techniques used include observation, interviews, learning outcome tests and documentation. The  learning outcomes show that the use of Powtoon media is effective in improving Islamic Religious Education learning at SMP Negeri 2 Bekasi. In the paired sample T test, seen from the sig. value, which is .000, which is smaller than alpha 0.05, then H0 is rejected. Thus, there is a very significant difference before and after the implementation of powtoon media in Islamic Religious Education subjects. Proven by the mean value, before the implementation of powtoon the average learning outcome was 62.10 and after the implementation of powtoon the average learning outcome became 87.05 Thus, the difference is very significant, before the implementation of powtoon the scores were low and after the implementation of powtoon media the PAI learning outcomes were higher.